Pulmonary Artery Pressure Profile in Atrial Septal Defect (ASD) Patients (Bangladesh Heart Journal, 2016)
The objective of this study was to see the incidence of pulmonary hypertension and its age distribution in atrial septal defect (ASD) patients in our population. A total of 58 ASD (secundum type) patients were included in the study. The diagnosis was done with echocardiography. Subsequently patients under went cardiac catheterization and their pulmonary artery (PA) mean pressure was measured. It was seen that pulmonary pressure increases with age. Severe PA hypertension (mean pressure > 40 mm Hg) was found in 14 patients (24.14%), age range was 10-55 years but most of them were more than 20 years old.Bangladesh Heart Journal 2015; 30(1) : 27-28